TOMSK POLYTECHNIC UNIVERSITY: PROMOTION TO WORLD ACADEMIC RANKINGS - Petr S. Chubik (Высшее образование в России)
The paper highlights the implementation of programme on National Research Tomsk Polytechnic University competitiveness enhancement in the group of top level world research and academic institutions and the promotion to TOP-100 of the world academic rankings. The strategic goal is TPU development as research university - one of the leaders in resource-efficient technologies, solving global problems of humanity on the way to sustainable development. Meeting a goal is planned through focusing the efforts on four basic development vectors: “Education”, “Research”, “Human Resources” and “Management”. The paper reveals the TPU undertakings for achievement of the assigned goals.